Role of piRNA biogenesis and its neuronal function in the development of neurodegenerative diseases - Sato, Kaoru; Takayama, Ken-ichi; Inoue, Satoshi (Frontiers in Aging Neuroscience, 2023)
Neurodegenerative diseases, such as Alzheimer’s disease (AD), Parkinson’s disease (PD), and amyotrophic lateral sclerosis (ALS), are caused by neuronal loss and dysfunction. Despite remarkable improvements in our understanding of these pathogeneses, serious worldwide problems with significant public health burdens are remained. Therefore, new efficient diagnostic and therapeutic strategies are urgently required. PIWI-interacting RNAs (piRNAs) are a major class of small non-coding RNAs that silence gene expression through transcriptional and post-transcriptional processes. Recent studies have demonstrated that piRNAs, originally found in the germ line, are also produced in non-gonadal somatic cells, including neurons, and further revealed the emerging roles of piRNAs, including their roles in neurodevelopment, aging, and neurodegenerative diseases. In this review, we aimed to summarize the current knowledge regarding the piRNA roles in the pathophysiology of neurodegenerative diseases. In this context, we first reviewed on recent updates on neuronal piRNA functions, including biogenesis, axon regeneration, behavior, and memory formation, in humans and mice. We also discuss the aberrant expression and dysregulation of neuronal piRNAs in neurodegenerative diseases, such as AD, PD, and ALS. Moreover, we review pioneering preclinical studies on piRNAs as biomarkers and therapeutic targets. Elucidation of the mechanisms underlying piRNA biogenesis and their functions in the brain would provide new perspectives for the clinical diagnosis and treatment of AD and various neurodegenerative diseases.